Estrategias inclusivas para promover el aprendizaje participativo en niños de cuarto año de educación básica. - Jurado Cardona , Maria Julieth (2025)
The school diversity presented by each educational institution throughout Latin America has led to being an issue of great importance nowadays at facing issues of discrimination or inequality at any academic level; because in the places where it is presented, it has led to generate diverse environments within each classroom, this is as a motive to the development and evolution of aspects of inequality and discrimination due to some special abilities that certain students may have; in such a way this investigation has focused mainly on children in the fourth year of basic education, mentioning that they are part of the study population; which allowed us to identify the most common weaknesses and problems that they could have within the classroom, through this, it was possible to propose some inclusive pedagogical strategies that favor the development of learning for all students in the basic education classroom, promoting equity and active participation; in addition, based on the lines above, it was possible to design different activities and diversified didactic resources that could favor the participation of all students, including those with specific educational needs; for all of that, various research methods were used, which were based on the qualitative method and had an exploratory and interpretive line of research; finally, a structured observation guide was carried out for the students and a structured interview directed to the teachers, where it was possible to know the different problems and weaknesses that the students present and therefore the difficulties with greater presence in the classrooms of fourth A and B were identified; with all the research carried out, it was possible to conclude that the most frequent problems are the lack of attention, the ease of distraction with games among students and the lack of acceptance when they are given an opinion or constructive comment about their actions, the lack of acceptance of parents to recognize that their children have a special problem; in addition, a positive trait prevails in both groups based on the development of group activities where an environment of trust and camaraderie is created and the participation of each student improves